Deep anterior chamber depth may be a risk factor for axial length growth in children - Cao, Huijie; Xiang, Yongguo; Cheng, Hong; Sun, Kexin; Zheng, Shijie; Du, Miaomiao; Gao, Ning; Zhang, Tong; Yang, Xin; Xia, Jiuyi; Wan, Wenjuan; Hu, Ke (Frontiers in Medicine, 2025)
To investigate and evaluate the progression of myopia and associated factors of axial length (AL) growth among children in Chongqing.This six-month prospective study was conducted on students in grades 1 to 8 at a school in Chongqing, China. All participants underwent a standard ophthalmologic examination including uncorrected visual acuity (UCVA), noncycloplegic refraction, AL, and corneal topography in March 2023. Six months later, the above examinations were repeated to obtain follow-up data. Visual habits questionnaire was gained to analyze the the correlation between the AL growth and vision-related behavior.Results: A total of 417 students from Chongqing were enrolled in this study. The myopia prevalence was higher in follow-up (38.6%) than in baseline (33.3%) and the AL was longer in follow-up than in baseline (23.69 ± 1.03mm vs. 23.57 ± 1.03mm, p < 0.001). The anterior chamber depth (ACD) in students with AL growth greater than or equal to 0.2 mm (3.16 ± 0.23mm) was deeper than that in students with AL growth less than or equal to 0.05 mm (3.02 ± 0.28mm, p = 0.001), lens thickness (LT) was thinner (3.29 ± 0.10mm vs. 3.33 ± 0.10mm, p = 0.004). Furthermore, ACD was positively correlated with AL growth. (r = 0.181, p < 0.001) .